In vitro study on glycation of plasma proteins with artificial sweeteners - Ali, Ahmad; Devrukhkar, Janhavi (Acta Biologica Szegediensis, 2016)
Glycation is a non-enzymatic reaction between the carbonyl groups of sugars and the amino groups of proteins, nucleic acids and lipids. This process results in the formation of early glycation products, which rearrange to form more stable advanced glycation end products (AGEs). Glycation has been linked to a number of diseases such as, Alzheimer’s, diabetes mellitus, cataract, Parkinson’s, physiological aging, etc. Synthetic sugar substitutes are known as artificial sweeteners. Like sugar, they contain reactive groups, which can interact with amino groups of macromolecules inducing damage by glycation. In the present study, non-enzymatic interaction between commercially available aspartame, saccharin and sucralose-based artificial sweeteners and amino acid lysine was performed in vitro. Also, plasma proteins like bovine serum albumin, human serum albumin, immunoglobulin G, blood clotting factors VIII and IX were incubated with aspartame and sucralose-based sweeteners. The results indicate that glycation reaction also occurs between proteins and these artificial sweeteners like sugars. This is the first report indicating involvement of artificial sweeteners in glycation.